COVID-19 and Food Insecurity in Latin America and the Caribbean - Hernández-Vásquez, Akram (2022)
The objective was to determine the prevalence of household food insecurity (FI) in Latin America and the Caribbean (LAC) during the COVID-19 pandemic. Secondary analysis was performed using the waves 1 to 3 of the 2020 COVID-19 High Frequency Phone Surveys in 13 LAC countries. The countries with the highest FI in the first wave were Honduras (60.3%), Peru (58.1%) and Ecuador (57.9%). Likewise, the countries with the greatest differences in the prevalence of FI between the first and last waves in percentage points (PP) were Peru (−29), Guatemala (−27.7) and Bolivia (−21.8). LAC countries face a great burden of FI.